Desiring Wanghuang: Live Streaming, Porn Consumption and Acts of Citizenship among Gay Men in Digital China. (July 2022) - Song, Lin
This paper investigates Chinese gay men's consumption of domestic pornography on international social network platforms following the country's anti-porn campaigns targeting live streaming. Set against the backdrop of China's illiberal digital landscape characterized by rapid platformization and evolving Internet governance, the paper draws on in-depth interviews with twenty-one Chinese young gay men to explore how they take advantage of digital platforms and algorithms to creatively and resiliently carve out a space for expressing same-sex desires in a precarious environment. It argues that, although these creative acts of sexual citizenship empower gay men in self-understanding and community-building, they are also critically limited by China's intertwining neoliberal and illiberal cultures.